A systematic review of asylum-seeking women's views and experiences of UK maternity care. (October 2019) - McKnight, P.; Goodwin, L.; Kenyon, S.
Highlights: Six studies were identified that explored asylum seekers views of maternity services. Pregnant asylum seekers face a distinct set of challenges from the home population, related to barriers to accessing care due to language issues and knowledge of maternity services. Mandatory provision of interpreter services, together with training for health care professionals could address urgent issues. More rigorous research is needed into the experiences of pregnant asylum seekers to more clearly identify potential interventions to improve care. Abstract: Objective: To explore and synthesise evidence of asylum-seeking women's experiences of maternity care in the UK. Design: A systematic review and thematic synthesis of peer-reviewed qualitative evidence. Relevant databases were searched from 2000 until 2018. Study quality was appraised using the Critical Appraisal Skills Programme (CASP) qualitative research appraisal tool. Setting and participants: UK-based studies which describe asylum-seeking women's views and experiences of maternity care. Findings: Six studies were included for thematic synthesis. Seven common themes emerged; 'Communication challenges', 'Isolation', Mental health challenges', 'Professional attitudes', Access to healthcare', 'Effects of dispersal' and 'Housing challenges'. The review indicated that pregnant asylum seekers face significant barriers to accessing maternity care due to practical issues related to the challenges of their status and lack of knowledge of maternity services, together with professional attitudes. Key conclusions and implications for practice: Mandatory provision of interpreter services, together with training for health care professionals could address urgent issues faced by pregnant asylum seekers. Further research and population-specific guidelines are needed to improve care for these women.